IMPLEMENTASI MANAJEMEN AUDIT SUMBER DAYA MANUSIA DI ERA GLOBALISASI MASYARAKAT EKONOMI ASIA (MEA) - S Suhairi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2018)
Changes in the globalization of the ASEAN economic community, we are ready not to be prepared to face in the pattern of internal and external environmental changes globally in ASEAN where the Asian economy is determined by free markets or mutual competition to grab the market at the top level globally agreed by ASEAN countries before. The Indonesian government must be able to focus and care for human resources, especially local employment (employee empowerment) with the quality of the workforce in line with the needs of the competitive advantage of the organization / company. For this reason, the parties involved in terms of government, education and society are moreover discouraged or design programs in the future, one of which is to re-audit resources that have standardized other countries, so that regional competition is beneficial for our country.